Global Uniform Asymptotic Stability of a Class of Switched Linear Systems with an Infinite Number of Subsystems - L. F. Araghi; A. A. Suratgar; E. Feizi (Abstract and Applied Analysis)
Stability of switching systems with an infinite number of subsystems is important in some structure of systems, like fuzzy systems, neural networks, and so forth. Because of the relationship between stability of a set of matrices and switching systems, this paper first studies the stability of a set of matrices, then and the results are applied for stability of switching systems. Some new conditions for globally uniformly asymptotically stability (GUAS) of discrete-time switched linear systems with an infinite number of subsystems are proposed. The paper considers some examples and simulation results.